2009
DOI: 10.1002/macp.200800569
|View full text |Cite
|
Sign up to set email alerts
|

The Spreading of Inkjet‐Printed Droplets with Varying Polymer Molar Mass on a Dry Solid Substrate

Abstract: An experimental study on the spreading of inkjet printed droplets of a polystyrene/toluene solution with varied molar masses on solid dry surfaces is presented. The polymer's number‐averaged molar mass was varied between 1.5 and 545 kDa, which also caused a variation in the viscosity from 0.6 to 1.7 mPa · s. The results were compared with theoretical models for droplet spreading and were found to fit with an error between 2 and 20% with the predictions. Furthermore, the in‐flight evaporation of the free‐fallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…The Oh of ink A and B was found to be 0.083 and 0.0284, respectively; this is in agreement with the theoretical predictions of Fromm [23] for a printable ink, however, it is not within the defined printable range of 0.1 < Oh < 1 [20]. However, other work [24,25] has also reported that inks outside of this region are printable, suggesting that this should not be a significant problem. The inks were deposited both on glass substrates (to determine the repeatability of the printed pattern), and onto carbon fibre reinforced Cycom 977-2 resin prepreg, in a hexagonal pattern (Fig.…”
Section: Microscopysupporting
confidence: 84%
“…The Oh of ink A and B was found to be 0.083 and 0.0284, respectively; this is in agreement with the theoretical predictions of Fromm [23] for a printable ink, however, it is not within the defined printable range of 0.1 < Oh < 1 [20]. However, other work [24,25] has also reported that inks outside of this region are printable, suggesting that this should not be a significant problem. The inks were deposited both on glass substrates (to determine the repeatability of the printed pattern), and onto carbon fibre reinforced Cycom 977-2 resin prepreg, in a hexagonal pattern (Fig.…”
Section: Microscopysupporting
confidence: 84%
“…[3] The drop then dries through solvent evaporation, [4] as shown in Figure 1. Recent studies [5] show that drop spreading and the final printed shape strongly depend on the viscosity, which in turn is a function of the molar mass of the polymer. More interestingly, the aforementioned group also found a printing height dependence of the final dried-drop diameter, which was a function of the polymer concentration.…”
Section: Inkjet Printing Processmentioning
confidence: 99%
“…Despite the difficulties in ensuring these conditions, all-printed transistors have been demonstrated using pentacene precursors and poly-4-vinylphenol (PVP) dielectric; [24] and polypyrrole and PVP-K60. [25] Additive printing of active layer inks (organic semiconductors dissolved in various solvents) such as poly [5,5 0 -bis(3-dodecyl-2-thienyl)-2, 2 0 -bithiophene] (PQT-12), [26] F8T2, [27] air-stable poly(3-hexylthiophene) (P3HT) derivatives, [28] 6,13-bis(triisopropylsilylethynyl) pentacene (TIPs pentacene), [29] other pentacene precursors and oligothophenes [30] have been demonstrated. Recently, carbon nanotubes (mobility $ 0.07 cm 2 V À1 s…”
Section: Thin-film Transistorsmentioning
confidence: 99%
“…Numerous studies have been conducted to improve the control of the inkjet deposition of polymers [18,19]. For example, it was demonstrated that the coffee ring effect can be effectively decreased and even suppressed by mixing solvents of different surface tensions [20].…”
Section: Introductionmentioning
confidence: 99%